2019
DOI: 10.1002/jctb.5997
|View full text |Cite
|
Sign up to set email alerts
|

Bioprocess development for (2R,3R)‐butanediol and acetoin production using very high polarity cane sugar and sugarcane molasses by a Bacillus amyloliquefaciens strain

Abstract: BACKGROUND: Efficient production of (2R,3R)-2,3-butanediol (BDO) and acetoin using the GRAS strain Bacillus amyloliquefaciens from very high polarity (VHP) cane sugar and sugarcane molasses could lead to the development of a sustainable industrial process. RESULTS:The effect of initial substrate concentration, nitrogen source, temperature, inoculum size and pH were evaluated in shake flask cultures. Batch bioreactor cultures showed that (2R,3R)-BDO production (up to 28 g L −1 ) with high yield (up to 0.43 g g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…22 This behavior was boosted under acidic conditions due that acetate was not detected on glucose consuming phase in batch cultivations, in contrast to neutral environments where acetate was produced and subsequently switched to acetoin and butanediol synthesis. [42][43][44] Higher acetoin and butanediol concentrations at pH 5 agrees with other studies that have reported upregulation of anabolic pathways for acetoin and butanediol production in acidic environments. 45 Consumption of acetoin and butanediol after glucose exhaustion could be related with a decrease in expression of systems required for catabolism of these compounds.…”
Section: Discussionsupporting
confidence: 90%
“…22 This behavior was boosted under acidic conditions due that acetate was not detected on glucose consuming phase in batch cultivations, in contrast to neutral environments where acetate was produced and subsequently switched to acetoin and butanediol synthesis. [42][43][44] Higher acetoin and butanediol concentrations at pH 5 agrees with other studies that have reported upregulation of anabolic pathways for acetoin and butanediol production in acidic environments. 45 Consumption of acetoin and butanediol after glucose exhaustion could be related with a decrease in expression of systems required for catabolism of these compounds.…”
Section: Discussionsupporting
confidence: 90%
“…inferring the reversible action of 2,3-BDO to acetoin upon glucose depletion in the broth (Maina et al, 2019). As shown in Fig.…”
Section: Effect Of Initial Substrate Concentrationmentioning
confidence: 80%
“…Concomitantly, acetoin accumulation increased up to 6.84±0.27 g/L after 2,3-BDO concentration reached a plateau, indicating the reversible action of butanediol dehydrogenase for NAD + /NADH redox balance (Maina et al, 2019). Ethanol (6.7±0.33 g/L), succinic acid…”
Section: 3-bdo Production From Pure Sugar(s)mentioning
confidence: 96%
“…A simple oxygen supply method based on constant agitation speed has been extensively used for BDO production. High agitation rates stimulate bacterial growth, acetoin and acetate accumulation leading to decreased BDO yields, whereas low agitation rate favor BDO and byproduct (namely succinate, lactate and ethanol) formation (Priya et al, 2016;Maina et al, 2019a). Cho et al (2015) reported BDO and acetoin production of 118.5 g L -1 and 42.1 g L -1 , respectively at 400 rpm with low by-product accumulation.…”
Section: Oxygen Supplymentioning
confidence: 99%